Why Perfluorocarbon nanoparticles encounter bottlenecks in clinical translation despite promising oxygen carriers? - De, Anindita; Jee, Jun Pil; Park, Young Joon (European Journal of Pharmaceutics and Biopharmaceutics, 2024)
Artificial Oxygen Carriers (AOCs) have emerged as ground-breaking biomedical solutions, showcasing tremendous potential for enhancing human health and saving lives. Perfluorocarbon (PFC)-based AOCs, in particular, have garnered significant interest among researchers, leading to numerous clinical trials since the 1980 s. However, despite decades of exploration, the success rate has remained notably limited. This comprehensive review article delves into the landscape of clinical trials involving PFC compounds, shedding light on the challenges and factors contributing to the lack of clinical success with PFC nanoparticles till date. By scrutinizing the existing trials, the article aims to uncover the underlying issues like pharmacological side effects of the PFC and the nanomaterials used for the designing, complex formulation strategy and poor clinical trial designs of the formulation. More over each generation of the PFC formulation were discussed with details for their failure in the clinical trials limitations that block the path of PFC-based AOCs' full potential. Furthermore, the review emphasizes a forward-looking approach by outlining the future pathways and strategies essential for achieving success in clinical trials. AOCs require advanced yet biocompatible single-component formulations. The new trend might be a novel drug delivery technique, like gel emulsion or reverse PFC emulsion with fluoro surfactants. Most importantly, well-planned clinical trials may end in a success story.
Keywords: Animals; Clinical Trials as Topic; Drug Carriers; Fluorocarbons; Humans; Nanoparticles; Oxygen; Translational Research, Biomedical; Artificial blood carriers; Challenges of PFC-AOCs; Clinical Trials; commercial PFCs; Perfluorocarbon nanoparticles